2016
DOI: 10.12998/wjcc.v4.i10.351
|View full text |Cite
|
Sign up to set email alerts
|

Increasing access to kidney transplantation for sensitized recipient through three-way kidney paired donation with desensitization: The first Indian report

Abstract: The combination of kidney paired donation (KPD) with desensitization represents a promising method of increasing the rate of living donor kidney transplantation (LDKT) in immunologically challenging patients. Patients who are difficult to match and desensitize due to strong donor specific antibody are may be transplanted by a combination of desensitization and KPD protocol with more immunologically favorable donor. We present our experience of combination of desensitization protocol with three-way KPD which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Internet‐based communication tools should be used to connect with other incompatible pairs . Our report showed that different KPD forms (Table ) can be successfully applied in any country with limited resources .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Internet‐based communication tools should be used to connect with other incompatible pairs . Our report showed that different KPD forms (Table ) can be successfully applied in any country with limited resources .…”
Section: Discussionmentioning
confidence: 91%
“…There is an accumulation of difficult‐to‐match pairs (for example, blood type O patients and non‐O donors). Compatible pairs ; combining KPD with desensitization or ABOiKT; expanding the number of acceptable mismatches; national , international and global kidney exchange ; the use of A2 donor to O patient such as in the Methodist KPD programme ; and computer allocations will improve the quality and quantity of match and transplant rates for difficult‐to‐match pairs. Internet‐based communication tools should be used to connect with other incompatible pairs .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported 2-way and 3-way KE combined with desensitization protocols to increase access to LDKT for sensitized recipients. 9,10 Recipient 1 was highly sensitized and unlikely to undergo LDKT with KE alone. He was able to undergo LDKT with a combination of KE and desensitization therapy.…”
Section: Discussionmentioning
confidence: 99%